Exploring the Relationship Between Depression and Bullying Among Indonesian Adolescents - Fatkhiyah, Latifa; Qutayan, Shadiya Mohamed Saleh Ba (Nusantara Science and Technology Proceedings, 2023)
Bullying has been identified as a serious problem around the world and has been linked with mental health problems such as depression. This study examined the relationship between bullying and depression among adolescents from three different schools and provinces in Indonesia. A total of 521 participants completed the Beck Depression Inventory-II (BDI-II) and answered two survey questions about bullying: whether they had witnessed bullying and whether they had ever experienced bullying. We found that most of the participants had a minimum level of depression (42%), while the majority of them reported having witnessed bullying (92%) and experienced bullying (61%). Among those who experienced bullying, the distribution of depression severity was as follows: severe (20.18%), moderate (19.87%), mild (21.76%), and minimum (38.17%). Interestingly, the relationship between depression severity and bullying involvement was not found to be statistically significant according to the Mann-Whitney test. These results indicate a high prevalence of bullying despite the relatively low prevalence of depression among the participant. The study's impact is limited due to the absence of information on other important factors that might affect the connection between bullying and depression such as family environment, social support, cultural influences, etc. Our findings give insight into how bullying and depression are related among Indonesian adolescents. However, the lack of a statistically significant relationship indicates that a careful interpretation is needed. We recommend future investigations to explore confounding factors to gain a comprehensive understanding of bullying's impact on depression.